2021
DOI: 10.1111/1541-4337.12820
|View full text |Cite
|
Sign up to set email alerts
|

Application of nonthermal processing technologies in extracting and modifying polysaccharides: A critical review

Abstract: Polysaccharides are natural polymer compounds widely distributed in plants, animals, and microorganisms, most of which have a broad spectrum of biological activities to promote human health. They could also be used as texture modifiers in food industry due to their excellent rheological and mechanical properties. Many researchers have shown that nonthermal processing technologies have numerous advantages, such as high extraction efficiency, short extraction time, and environmental friendliness, in the extracti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 124 publications
0
8
0
Order By: Relevance
“…Some special structural characteristics of polysaccharides are beneficial for activating NK cells, which has been confirmed by many studies [ 40 , 41 ]. For instance, polysaccharides with glucose [ 24 , 42 ], mannose [ 43 , 44 ] or N -acetyl-d-glucosamine [ 24 ] are more easily recognized and connected by complement receptor type 3 (CR3) on NK cells [ 45 ]. Vetvicka et al [ 46 ] reported that a soluble polysaccharide, SZP (10 kDa, 95% mannose and 5% glucose), had a higher affinity for CR3 than many soluble β-glucans (20–1000 kDa).…”
Section: Resultsmentioning
confidence: 99%
“…Some special structural characteristics of polysaccharides are beneficial for activating NK cells, which has been confirmed by many studies [ 40 , 41 ]. For instance, polysaccharides with glucose [ 24 , 42 ], mannose [ 43 , 44 ] or N -acetyl-d-glucosamine [ 24 ] are more easily recognized and connected by complement receptor type 3 (CR3) on NK cells [ 45 ]. Vetvicka et al [ 46 ] reported that a soluble polysaccharide, SZP (10 kDa, 95% mannose and 5% glucose), had a higher affinity for CR3 than many soluble β-glucans (20–1000 kDa).…”
Section: Resultsmentioning
confidence: 99%
“…Natural polysaccharides are widespread in organisms from prokaryotes to eukaryotes, serving as critical components involved in various life activities [ 44 , 45 ]. They have been used for decades as building blocks to create functional biomaterials and can be modified to formulate derivatives for applications in delivery carriers [ 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…The efficient extraction of functional components from target tissues or cells is a major problem prior to fermentation. The raw materials are usually pressed and macerated for a long time to extract their active ingredients such as sugar and polyphenols in traditional brewing, thus improving the yield and quality of fermented wine ( 32 , 33 ). PEF is adopted as a new way for promoting the extraction of active ingredients, shortening the immersion time, and promoting alcohol fermentation.…”
Section: Applicability Of Pulsed Electric Fieldmentioning
confidence: 99%